Peningkatan Daya Saing Daerah Melalui Upaya Pembangunan Kompetensi Kepemimpinan Pejabat apublik Daerah - Rahmat, Rahmat (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
The role of leaders in improving local government competetitiveness is apparently significant and determinant. The focus, therefore, is to find ways of improving leaders capacity in creating and designing policies that support and develop local competitiveness power among communities. This article discusses the leaders competence development strategies that are closely linked with the efforts to improve local competitiveness. The essay begins with a case of Indramayu regent who has been _ to certain extent- succesful in improving Indramayu’s competitiveness among other regencies in West Java. The discussions is then focused on the concept of competetitivess and is closed with several strategies to improve leaders competence.